Revitalization of Ngaju Dayak Cultural Heritage through the Development of Traditional Mandau Weapon Designs with Djata Motifs - Yusma Pratiwi, Endah; Asmoro Girindraswari, Nawung; Aulia Mayangsari, Marrisa; Arie Astuti, Andi (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
This study aims to formulate efforts to revitalize the cultural heritage of the Dayak Ngaju through the development of the traditional Mandau weapon design incorporating the Djata motif. The Mandau weapon is an essential part of the cultural identity of the Dayak people, passed down from generation to generation. Amid the currents of modernization, efforts to preserve and revitalize local culture, including traditional weapon design, are necessary to prevent the loss of its cultural significance and philosophical values. This research examines the historical and aesthetic aspects of the Mandau, integrating the Djata motif as a symbol of protection and strength. The method includes an interview with a Mandau weapon craftsman, documentation, and a visual analysis of traditional Dayak motifs. The results indicate that the Djata motif in the Mandau design can strengthen cultural values and enrich the traditional art repertoire of Dayak Ngaju.